2014
DOI: 10.1111/peps.12078
|View full text |Cite
|
Sign up to set email alerts
|

Double Jeopardy Upon Resumé Screening: When Achmed Is Less Employable Than Aïsha

Abstract: Applicants belong to multiple categories (e.g., male, ethnic minority) and a complex set of factors affects category activation and inhibition when making hiring decisions. Two field experiments with recruiters who regularly engage in resumé screening showed that the role of multiple categories (applicants' ethnicity and sex) in discrimination depended on job type and prejudice. Specifically, in both low-and high-demand (i.e., complex) jobs, Arab women were rated more favorably than Arab men, particularly when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 92 publications
(140 reference statements)
4
53
0
Order By: Relevance
“…For example, an analysis of over 500,000 employees revealed that those belonging to multiple minority groups (e.g., having both a disability and belonging to a racial minority) received lower pay than employees belonging to a single minority group (Woodhams, Lupton & Cowling, 2013). Similar results emerged in an analysis of payment towards employees that were both racial and gender minorities (Greenman & Xie, 2008), and a field experiment found that applicants with multiple stigmatized identities were rated as less employable than applicants with a single threat-related identity (Derous, Ryan & Serlie, 2015).…”
Section: Existing Evidencesupporting
confidence: 61%
“…For example, an analysis of over 500,000 employees revealed that those belonging to multiple minority groups (e.g., having both a disability and belonging to a racial minority) received lower pay than employees belonging to a single minority group (Woodhams, Lupton & Cowling, 2013). Similar results emerged in an analysis of payment towards employees that were both racial and gender minorities (Greenman & Xie, 2008), and a field experiment found that applicants with multiple stigmatized identities were rated as less employable than applicants with a single threat-related identity (Derous, Ryan & Serlie, 2015).…”
Section: Existing Evidencesupporting
confidence: 61%
“…Per social identity theory (Ashforth and Mael ) and related research, recruiters’ characteristics (e.g. ethnicity, gender) interact with the information provided in the résumés and influence the inference process (Derous, Ryan and Serlie ). Following the similarity‐attraction paradigm (Graves and Powell ), the extent to which the applicant shares some personal characteristics (such as earlier academic performance and engagement in ECAs) with the recruiter might influence the perceived employability of the former by the latter.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…The broader psychology domain has only recently acknowledged the utility of intersectional research despite its prevalence in other related research domains. Still, this is not to disparage or discount these cases, as they lay the foundations for the present discussion (e.g., Berdahl & Moore, 2006;Derous, Ryan, & Serlie, 2014). Despite these findings, the existing I-O psychology literature has largely overlooked how intersecting identities critically affect employees' workplace experiences.…”
Section: Intersectionality Definedmentioning
confidence: 90%